Vegetation characteristics of the Javan slow loris habitat in Mount Masigit Kareumbi Protected Area, West Java, Indonesia - ANESHA ALLASSELCIDA; ELHAM SUMARGA; SOFIATIN SOFIATIN (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Allasselcida A, Sumarga E, Sofiatin. 2024. Vegetation characteristics of the Javan slow loris habitat in Mount Masigit Kareumbi Protected Area, West Java, Indonesia. Biodiversitas 25: 2512-2520. Habitat loss and degradation are major threats to the conservation of endemic wildlife in Indonesia, owing to the high rates of deforestation over the past decades. Most of these endemic animals are now at risk of extinction. Javan slow loris (Nycticebus javanicus) is a primate endemic to Java Island and is currently classified as critically endangered by the IUCN. This study analyzes four key aspects of the loris' habitat in Mount Masigit Kareumbi Protected Area (MMKPA), West Java: plant diversity, vegetation community structure and composition, plant species as food sources, and canopy density. A vegetation survey was conducted in three research sites using 41 nested plots measuring 20x20 m for trees, 10x10 m for poles and shrubs, 5x5 m for saplings, and 2x2 m for herbaceous plants. Data on plant species, diameter at breast height (DBH), and abundance (number of individuals) were collected within each plot. Forest Canopy Density (FCD) was mapped using Landsat 8 RAW Imagery and Landsat 8 TOA Reflectance Imagery, involving calculating several indices: Advanced Vegetation Index (AVI), Bare Soil Index (BI), Shadow Index (SI), and Thermal Index (TI). This study identified 104 plant species from 40 families across the three studied sites with dominant tree species were Pinus merkusii, Schima wallichii, Actinodaphne procera, Pinanga coronata, Miconia crenata, and various Setaria species. The diversity index at the three locations ranged from 3.02 to 3.41. This study found 35 species, including the dominant tree species, which served as food sources for slow lorises. The primary food sources available to slow lorises are sap (92.4%), followed by fruit (3.9%) and flowers/nectar (3.7%). The results of FCD analysis indicated that 83% of MMKPA has a "high" category, suggesting the presence of a continuous branch network that facilitates the easy movement of Javan slow loris. This information can be used to develop strategies for improve habitat management in the area, such as enriching fruit-bearing crops to increase food diversity.